Organizaciones políticas no institucionalizadas y Estado de Derecho en el Perú post-Fujimori: Una propuesta para la investigación - Cameron, Maxwell A. (2013)
Political science literature has focused itself mostly on the «pro-democracy» role of political parties, identifying them as essential instruments for representation. We agree, but we believe this is not the only aspect to focus on. Democratic parties do not only achieve power through regular elections, but they also aspire to rule within a democratic regime. In that sense, the functioning of political parties can be analyzed not only in terms of their contribution to electoral competition. In order to fulfill their democratic functions, parties need a strong constitutional order that allows them to provide two goods: the achievement of power through legalways and good governance within the Rule of Law.